ANALISIS PENGARUH BRAND ASSOCIATIONS, BRAND AWARENESS, DAN BRAND IMAGE TERHADAP LOYALITAS MEREK DENGAN EKUITAS MEREK SEBAGAI VARIABEL INTERVENING PADA SEPATU OLAHRAGA NIKE DI KOTA SEMARANG - Putri, Novya Kurnianing; Mudiantono, Mudiantono (Faculty of Economics and Business Diponegoro University, 2016)
This study aimed to analyze the effects arising from the brand associations, brand awareness, and brand image on brand equity and its influence on brand loyalty from sport shoes brand Nike. The variables used in this study is brand associations, brand awareness, and brand image as an independent variable, then the brand equity as an intervening variable and brand loyalty as the dependent variable. The sample in this study were 200 respondents that came from residents in the city of Semarang, who ever used and purchased sport shoes brand Nike.The method used is purposive sampling by distributing questionnaires to the respondents. In this study developed a theoretical model to propose seven hypotheses to be tested using analysis tools Structural Equation Modeling (SEM) which is operated through a program AMOS 20.0. Based on the research of data processing SEM for full model has met the criteria of goodness of fit as follows, the value of chi-square = 100,855; probability = 0,058; RMSEA = 0,041; CMIN/DF = 1,261; GFI = 0,913; TLI = 0,986; CFI = 0,989; NFI = 0,951, and a marginal criteria which is AGFI = 0,870. With the result that it can be said that this model is feasible to be used. The results showed that the brand loyalty can be improved by increasing brand awareness affect the brand equity as a determinant of success increase brand loyalty.